High-Q lattice mode matched structural resonances in terahertz metasurfaces - Xu, Ningning (2016)
The quality (Q) factor of metamaterial resonances is limited by the radiative and non-radiative losses. At terahertz frequencies, the dominant loss channel is radiative in nature since the non-radiative losses are low due to high conductivity of metals. Radiative losses could be suppressed by engineering the meta-atom structure. However, such suppression usually occurs at the fundamental resonance mode which is typically a closed mode resonance such as an inductive-capacitive resonance or a Fano resonance. Here, we report an order of magnitude enhancement in Q factor of all the structural eigenresonances of a split-ring resonator fueled by the lattice mode matching. We match the fundamental order diffractive mode to each of the odd and even eigenresonances, thus leading to a tremendous line-narrowing of all the resonances. Such precise tailoring and control of the structural resonances in a metasurface lattice could have potential applications in low-loss devices, sensing, and design of high-Q metamaterial cavities.